Faking ADHD? Symptom Validity Testing and Its Relation to Self-Reported, Observer-Reported Symptoms, and Neuropsychological Measures of Attention in Adults With ADHD. Issue 3 (February 2018) - Hirsch, Oliver; Christiansen, Hanna
Objective: To compare ADHD patients who failed a symptom validity test with those who passed the test to explore whether there are signs of negative response bias on group level.Method: In our outpatient department, 196 adults were diagnosed with ADHD using a comprehensive diagnostic strategy featuring a detailed clinical history, clinical interview, observer rating, several self-rating scales, and neuropsychological attention tests. The Amsterdam Short Term Memory Test (AKGT) was applied as a symptom validity measure.Results: Sixty-three patients (32.1%) scored below the AKGT cutoff level. The two groups did not significantly differ regarding self-report and observer ratings. Those who failed the AKGT had higher reaction time variabilities in selective, auditory and visual divided attention, and higher omission errors in sustained attention.Conclusion: We found no strong indicators for negative response bias in ADHD patients who failed a symptom validity test. New measures and approaches to detect feigned ADHD should be developed.